2016
DOI: 10.1103/physrevlett.116.103602
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Optical Cross Section via Collective Coupling of Atomic Dipoles in a 2D Array

Abstract: Enhancing the optical cross section is an enticing goal in light-matter interactions, due to its fundamental role in quantum and nonlinear optics. Here, we show how dipolar interactions can suppress off-axis scattering in a two-dimensional atomic array, leading to a subradiant collective mode where the optical cross section is enhanced by almost an order of magnitude. As a consequence, it is possible to attain an optical depth which implies high-fidelity extinction, from a monolayer. Using realistic experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
218
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(227 citation statements)
references
References 57 publications
9
218
0
Order By: Relevance
“…Their miniaturization is fundamentally limited by the optical wavelength in the case of dielectric mirrors and photonic crystals (1) or by the skin depth for metallic mirrors (2). Recently, resonant scattering has emerged as a method for overcoming these limitations and for controlling light at the atomic scale (3)(4)(5)(6)(7)(8)(9)(10)(11). For instance, highly reflective mirrors based on individual quantum emitters have been demonstrated by coupling them to optical cavities and nanophotonic waveguides (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their miniaturization is fundamentally limited by the optical wavelength in the case of dielectric mirrors and photonic crystals (1) or by the skin depth for metallic mirrors (2). Recently, resonant scattering has emerged as a method for overcoming these limitations and for controlling light at the atomic scale (3)(4)(5)(6)(7)(8)(9)(10)(11). For instance, highly reflective mirrors based on individual quantum emitters have been demonstrated by coupling them to optical cavities and nanophotonic waveguides (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Such resonant mirrors feature very unusual properties due to their extraordinary nonlinearity down to the single-photon level (3)(4)(5)(6)(7)(8). A two-dimensional (2D) layer of emitters, such as atomic lattices or excitons (9)(10)(11), has also been predicted to act as an efficient mirror when the incident light is resonant with the resonance frequency of the system. Such atomically thin mirrors represent the ultimate miniaturization limit of a reflective surface, and could enable unique applications ranging from quantum nonlinear optics (9-11) to topological photonics (12,13).…”
mentioning
confidence: 99%
“…These narrow linewidths have a dominant contribution from radiative decay of ∼1.5 meV for MoSe 2 [11,12]. Motivated by these developments, we previously analyzed the optical response of a monolayer TMD theoretically [13] and showed that it realizes an atomically thin mirror [13][14][15].…”
mentioning
confidence: 99%
“…By calculating the scattered electric field across output and input collection lenses, we measure directly the extinction of a single monolayer of atoms, showing that at particular lattice spacings, an incident light beam is almost completely reflected. This work was published in [67].…”
Section: Infinite Limit and Reduction In Complexitymentioning
confidence: 99%
“…We will be following the approaches taken in [101,134]. See as well our paper [67] and the corresponding Supplemental Material.…”
Section: Realistic Beam Focussingmentioning
confidence: 99%